Imobilização de α-galactosidase de Aspergillus niger em resina de troca iônica Duolite A-568 - Costa, Henrique Coutinho de Barcelos (2012)
Immobilized enzymes provide many advantages when compared to the usage of their free forms. Among these ones, remarkable advantages are the possibility of the biocatalyst reusability, easy separation at the end of the process, its usage in continuous way and the enhancement of its stability. This work was performed aiming the immobilization of the α-galactosidase enzyme from Aspergillus niger in ion exchange resin and the evaluation of its catalytic activity. Firstly, tests were performed in five different resins: Amberlite 252-Na, Dowex Marathon A, Dowex Marathon C, Duolite A-568 e Duolite S-761. According to the results, Duolite A-568 was chosen as the best support. Therefore, studies were done aiming the optimization of the immobilization process in this resin. Glutaraldehyde 1% (v/v) was used before the enzyme adsorption process and it enhanced the operational stability of the immobilized enzyme. Preliminary tests did not showed difference for the immobilization process at the temperatures of 25 and 40°C. A full factorial design and a central composite design were performed to study the best immobilization conditions varying the pH, the α-galactosidase concentration and the immobilization time. The results led to use the following immobilization conditions: pH 4.5; 15 g/L of α-galactosidase and 3 hours of immobilization. The temperature of maximum activity occurred at 60°C for both free and immobilized enzyme. The activation energy calculated by linear adjustment of Arrhenius equation was 5.66 kcal/mol for soluble α-galactosidase and 4.48 kcal/mol for immobilized α-galactosidase. The optimum pH range obtained for free enzyme was 4.0-5.0 and for immobilized enzyme it was 3.0-6.0. The immobilization process improved the α-galactosidase activity in alkaline pHs. Analysis of pH stability showed that both forms of enzyme were resistant for the pH ranges studied (3.5 to 7.5 for free and 3.0 to 8.0 for immobilized). However, the thermal stability of the biocatalyst immobilized in the support decreased. The kinetic studies without inhibition showed closed values of maximum speed (Vmax) for both enzyme forms (194.5 U for free and 187.7 U for immobilized). Although, the Michaelis-Menten constant (Km) of immobilized enzyme was higher than the free one (18.8 and 12.5 g/L, respectively). The hydrolysis reaction of raffinose was inhibited by the addition of the reaction products, sucrose and galactose, and the results of inhibition by galactose pointed for the competitive inhibition type. Then, storage tests of immobilized α-galactosidase showed that the enzyme maintained its activity even after 145 days when kept at the temperature of 4°C.